Subject indexing of local lore documents: a technological aspect (a case of Kemerovo Regional Scientific Library named after V. D. Fyodorov) - T. P. Rudakova; O. Ya. Sakova (Библиосфера)
The article considers subject indexing of local history documents with the technological approach point of view. It gives characteristics of each element component structure of the technological process of local lore documents subject indexing in Kemerovo Regional Scientific Library named after V. D. Fyodorov.